THE COVID-19 PANDEMIC'S EFFECT ON RUBBER PRICES AT THE FARMER LEVEL IN SOUTH SUMATRA PROVINCE - Audina, Mitha; Mulyana, Andy; Antoni, Mirza (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the influence that affects changes in rubber prices at the farmer level before and during the covid-19 pandemic. This study uses panel data for 24 (twenty-four) months, from January 2019 to December 2020. The response variable (Y) is the price of rubber at the farmer level in South Sumatra Province obtained from 28 UPPB (Rubber Processing and Marketing Units). The analysis tool used is a multiple regression of panel data with the help of RStudio software. The results of the analysis using the Random Effect Model (REM) method showed that international rubber prices, rupiah exchange rates against the US dollar, world crude oil prices and synthetic rubber prices were both real influences on rubber prices at the farmer level, both before and during the covid-19 pandemic. Changes in international rubber prices during the covid-19 pandemic had a much greater positive impact on rubber prices at the farmer level than before the pandemic, while the change in rupiah exchange rate against the US dollar and world crude oil and synthetic rubber prices was smaller. Keywords: Covid-19, Price of Rubber, REM, Panel Data